PROPERTY RELATIONS IN KYRGYZ FAMILY: LEGAL ASPECTS - Murzabekova, Zh.T.; Nasbekova, S.K.; Osmonalieva, N.Zh. (Scientific Journal of Pedagogy and Economics, 2020)
The article provides legal analysis of features of family property relations in the custom law of the Kyrgyz people and the legislation of the Kyrgyz Republic. Using analysis, synthesis, legal and historical law methods, the Matrimony and Family Code of the Kyrgyz SSR of 1969, the Family Code of the Kyrgyz Republic of 2003, the Code of Laws on Civil Status Acts, Matrimony, Family and Fiduciary Law of the RSFSR of 1918, The Code of Laws on Marriage, Family and Fiduciary of the RSFSR of 1926, The Ordinance of the President of the Kyrgyz Republic dated January 26, 2012 No. 17 “On declaring 2012 the Year of Family, Peace, Concordance and Mutual Forgiveness” and Family Support and Child Protection Program for 2018 - 2028 of Government of the Kyrgyz Republic were studied. The article analyzes relevant theoretical and practical issues related to common property of spouses, separate property of spouses, relations between parents and children for joint ownership and use of each other's property, alimony responsibility of family members and property relations of factual spouses. According to the author, legal norms regulating property relations in family are important when courts consider cases in sphere of protection of property rights of family members. In particular, the authors came to the conclusion in the Kyrgyz Republic the legal regulation of property relations in family is basis for resolving contentious issues in the family law.